A map of human protein interactions derived from co‐expression of human mRNAs and their orthologs - Arun K Ramani; Zhihua Li; G Traver Hart; Mark W Carlson; Daniel R Boutz; Edward M Marcotte (Molecular Systems Biology)
Abstract The human protein interaction network will offer global insights into the molecular organization of cells and provide a framework for modeling human disease, but the network's large scale demands new approaches. We report a set of 7000 physical associations among human proteins inferred from indirect evidence: the comparison of human mRNA co‐expression patterns with those of orthologous genes in five other eukaryotes, which we demonstrate identifies proteins in the same physical complexes. To evaluate the accuracy of the predicted physical associations, we apply quantitative mass spectrometry shotgun proteomics to measure elution profiles of 3013 human proteins during native biochemical fractionation, demonstrating systematically that putative interaction partners tend to co‐sediment. We further validate uncharacterized proteins implicated by the associations in ribosome biogenesis, including WBSCR20C, associated with Williams–Beuren syndrome. This meta‐analysis therefore exploits non‐protein‐based data, but successfully predicts associations, including 5589 novel human physical protein associations, with measured accuracies of 54±10%, comparable to direct large‐scale interaction assays. The new associations’ derivation from conserved in vivo phenomena argues strongly for their biological relevance.